Effects of nutritional status on mitochondrial Ca2+ handling - Menezes Filho, Sérgio Luiz de (2019)
Mitochondria are central players in cell metabolism, responsible for the vast majority of ATP production in most cells. Although originally thought to be passive organelles focused only in keeping cellular ATP at adequate levels, complex interplay between mitochondrial function and cell signaling has been largely recognized over the last decades. Not surprisingly, given their role, changes in nutritional status promoted by chronic interventions like caloric restriction or short-term situations like fasting in animals or nutrient deprivation in cultured cells are one of the main factors that can activate those signaling mechanisms. One particular way in which this mitochondria-cell crosstalk can occur is through mitochondrial Ca2+ handling, a process in which Ca2+ signals generated by the cell are able to translate into elevations in mitochondrial matrix [Ca2+] due to the presence of the mitochondrial Ca2+ uniporter in the organelle. While the impact of mitochondrial Ca2+ handling on cellular function has been widely studied, the conditions which can modulate the process of mitochondrial Ca2+ handling itself are still not well characterized. In this work, we sought to test the effects of different interventions linked to nutritional status on mitochondrial Ca2+ handling. We found that caloric restriction, physiological fasting and modulations of mitochondrial dynamics resulted in modulation of mitochondrial Ca2+ handling through changes in their maximal Ca2+ retention capacity or Ca2+ uptake rates. These changes were, measured by following mitochondrial Ca2+ uptake using different strategies, employing the fluorescent Ca2+ probe Ca2+ Green 5N for experiments in isolated mitochondria and permeabilized cells and the cytosolic probe Fura2-AM in intact cells. Caloric restriction resulted in higher calcium uptake and retention in liver mitochondria, protecting against pathological conditions of Ca2+ overload during ischemia/reperfusion. On the other hand, overnight and short term fasting resulted in lower mitochondrial Ca2+ retention and oxidative phosphorylation capacity in the liver. Modulating mitochondrial morpholoy in C2C12 myoblasts showed that more fragmented mitochondria were less capable of taking up Ca2+, while more fusioned mitochondria showed the opposite phenotype. This modulation in Ca2+ handling through changes in mitochondrial morphology interfered with the process of Store-Operated Ca2+ entry in the cells, showing that these modulations can have impacts in physiological contexts as well. Overall, this work both establishes novel mechanisms of modulation of mitochondrial Ca2+ handling and demonstrates their relevance both in pathology and normal cellular physiology.